Counseling women with breast cancer : a guide for professionals - Keitel, Merle A. (Women's mental health and development ;, 2000)
'Counseling Women With Breast Cancer' is a comprehensive guide to the issues surrounding breast cancer and the processes involved in mental and emotional coping and healing.